Advances in abdominal surgical oncology - Luque-Vásquez V., Carlos E. (2025)
The rapid technological evolution of laparoscopic and robotic surgical systems, together with the emergence ofnovel and highly effective antineoplastic therapies-driven by rigorous basic and clinical research-and a refinedunderstanding of surgical anatomy, is continuously reshaping oncologic surgical techniques. This transformation ischaracterized by the implementation of increasingly individualized neoadjuvant protocols, tailored to specific tumorbiology and patient profiles. These strategies have enabled the conversion of initially unresectable or borderline resectablegastrointestinal tumors into resectable disease, amenable to standardized surgical resection techniques based on highcentral vascular ligation and complete mesenteric excision, consistent with the organ's embryological origin.